Relevance for tourist visiting decisions – destination branding vs destination image: Case study from Lariti Beach, Bima Regency - ZA, Saida Zainurossalamia; Tricahyadinata, Irsan (Turyzm/Tourism, 2025)
Today, there are disciplines that concentrate on tourism, some of which highlight a tourist’s visiting decision; this is not only associated with the brand or reputation of a destination but also its image. From this premise, this study aims to find the relationship between destination branding and destination image on tourists’ visiting decisions. With a focus on tourists visiting Lariti Beach, Bima Regency (Indonesia), data collection via interviews based on non-probability sampling techniques were made. Using the partial least squares (PLS) method, the results of the study reveal that both destination branding and destination image affect tourists’ visiting decisions systematically. When compared, destination branding is the more important instrument for increasing visiting decisions compared to image. Therefore, this research opens space and attention for further studies to consider destination image as a critical function in stimulating visiting decisions. Future implications include tourism policies that lead to optimal branding and image.